Packed red cell blood transfusion practices review in medical oncology unit in a tertiary cancer center, South India - Angadi, Veerendra; Nandennavar, Manjunath; Karpurmath, Shashidhar V.; Jacob, Roshan; Donekal, Yamini (International Journal of Research in Medical Sciences, 2019)
Background: Anaemia is a very common complication in cancer patients. Up to 60% of solid tumor patients and 70-90% of patients receiving myelosuppressive chemotherapy have anaemia. Pathophysiology of anaemia in cancer patients is multifactorial. The treatments for cancer related anaemia include Erythropoietin Stimulating Agents (ESAs), iron supplementing therapies (intravenous iron, oral iron) and blood transfusion. There are various safety concerns regarding usage of ESAs; also, their usage is less in India due to cost factor. There is scant literature regarding blood transfusion practices in patients undergoing chemotherapy. Methods: Patients diagnosed with cancer and patients receiving chemotherapy were included in the study. Retrospective case record review of cancer patients who received chemotherapy between January to March 2019 was done. Type of malignancy, presence of symptoms related to anemia and trigger for packed red cell transfusion were recorded. Results: Among 342 patients received total of 1365 cycles of chemotherapy in this time period. Mean age of patients was 46 years. 46 of the 342 patients received blood transfusion. Only 13% of the patients had symptoms of anemia like weakness and fatigue the average hemoglobin level at which transfusion was given was 6 gm/dL. Conclusions: Packed Red blood cell transfusion was usually administered at Hb <7 gm/dL. Very few patients reported anaemia related symptoms prior to transfusion. No patient received erythropoietin. Further data is needed from other tertiary cancer centres to understand the blood transfusion practices in Indian cancer patients undergoing chemotherapy.